A Second Species of Serbanibathynella (Bathynellacea: Bathynellidae) from South India. Issue 3 (1st May 2014) - Rao Totakura, Venkateswara; Ranga Reddy, Yenumula
Abstract: Serbanibathynella secunda n. sp., the second representative of the previously monotypic Indian genus Serbanibathynella Ranga Reddy and Schminke, 2005, is described. It was collected on several occasions from both alluvial sediments of the hyporheic zone as well as farm bores in the riparian zone of the coastal deltaic belt of the Rivers Krishna and Godavari in Andhra Pradesh state, southeastern India. The new species fulfills almost all the principal generic criteria of Serbanibathynella Ranga Reddy and Schminke, 2005, but is distinctly different from the type species, Serbanibathynella primaindica Ranga Reddy and Schminke, 2005, in several essential features: uropodal sympod has inhomonomous vs. homonomous row of spines; mandible has four vs. three pointed teeth on the first segment of 3-segmented palp; maxillular proximal segment with three vs. four setae; setal formula of maxilla 5(1)-4-5-5 vs. 7-4-7-6; female Th VIII uniramous vs. biramous, with 2 vs. 2 + 1 setae. These and all other salient differences between the two species are tabulated. All in all, the new species shows trends of morphological simplification vis-à-vis its congener. A note on the ecology and distribution of the new species is also added.